AN OVERVIEW OF KNOWLEDGE, ATTITUDE AND BEHAVIOR ABOUT USING SELF PROTECTIVE EQUIPMENT IN TOLL ROAD CONSTRUCTION WORKERS PT.X, LAMPUNG IN OCTOBER 2018 - Winata, Susanty Dewi; Kurniawan, Hendrik; Sutanti, Yosephin Sri; Purnamawati, Purnamawati; Situmorang, Priscilla Revina (Jurnal MedScientiae, 2024)
The behavior of using Personal Protective Equipment (PPE) in construction sector workers in Indonesia is still not good, this is indicated by the still high mortality and disability due to workplace accidents. There are still many workers who do not use PPE when working based on several factors, including the lack of company policy and supervision and aspects of the workers themselves. The purpose of this study was to see an overview of the knowledge, attitudes and behavior of construction workers about the use of PPE in PT. X, Lampung in 2018. The research design used in this study was a cross-sectional design that was descriptive in nature. This study used a sample of 50 people and analyzed univariately. The results of this study show a picture of knowledge, attitudes and good behavior about the use of PPE. In addition, the highest age for workers is> 30 years, the highest level of education is Higher Education and the lowest is elementary school and the highest level of education is high school / vocational school, the highest period of employment is ≤ 10 years. From the results of this study it can be concluded that respondents have a high level of awareness about the importance of using PPE to avoid the risk of workplace accidents.